Kesiapsiagaan Perpustakaan Dalam Menghadapi Bencana Banjir (Studi Kasus pada Perpustakaan Daerah Kabupaten Hulu Sungai Tengah) - Ahdie Anwary (Jurnal Kewarganegaraan, 2023)
Abstrak This study will discuss 3 components in the disaster management cycle, namely disaster preparedness (preparedness), disaster response (response) and disaster recovery (recovery). Hulu Sungai Tengah in mid-January 2021, Law No. 24 of 2007 explains the definition of disaster which means a series of events or events that disrupt and threaten people's lives resulting in losses, damage, causing casualties, property losses and having an impact on psychology and individuals or society. Furthermore, disasters are categorized into two, namely natural disasters and non-natural disasters. Research on library preparedness in dealing with flood disasters (case study at the regional library in the Upper Sungai Tengah district) uses a qualitative descriptive approach (qualitative research methods). Where this study tries to understand the phenomenon in actual conditions, tries to describe what happened in its entirety and at play It is important for libraries to have plans and readiness if floods will occur in the future, as an early detection and safety net for libraries to respond quickly, but This preparatory plan is rarely considered as an important thing for libraries because they think that it is always safe and that disasters rarely occur which result in less alertness to these disasters. on the library. It is necessary to form a quick response task force team if disaster occurs again, furthermore the library in terms of buildings and infrastructure is very good and capable because it has a fairly new building and has 3 floors. Semester or quarterly training is important to be launched in order to have trained human resources in the event of a disaster. Keywords: Kesiapsiagaan, Perpustakaan, Bencana, Banjir, Mitigasi Bencana,